Nano-indentation of hybrid silica coatings on surgical grade stainless steel - Ballarre, Josefina (2008)
Hybrid silica-based coatings with tetraethoxysilane (TEOS), methyltrietoxysilane (MTES), hydroxyethyl-methacrylate (HEMA) and methacrylopropyl-trimethoxysilane (γMPS) as precursors, were employed to improve the performance of stainless steel used as orthopaedic material. Mechanical properties of the films, such as Young's modulus and hardness, were studied using the load and depth sensing indentation technique known as nano-indentation. The elastic/plastic and creep behaviours were also analyzed. Coatings with a high proportion of organic components (HEMA, γMPS) presented a more plastic response compared to the more vitreous coatings (containing only TEOS and MTES). They also showed the lowest Young's modulus and hardness. Therefore, the more vitreous coatings presented lower creep deformation that increased with the load applied.